2020
DOI: 10.34117/bjdv6n4-315
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive and productive performance of cows of the Tabapuã breed

Abstract: The objective of this study was to evaluate the performance of 369 Tabapuã cows, from Copacabana farm, in Xambrê-PR, Brazil. Data was submitted to ANOVA, means assessed by the Duncan test, gestation rates and percentages by Chi square (p <0.05). 76.56% (369/482) of the cows presented age (μ + σ) of 6.80 + 2.93, and the gestation rate (TG) of the third service, the final TG and the service period varied with the age of cows (p <0.05). The TG of the first and second service, the final TG, the percentage of empty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
0
1
Order By: Relevance
“…This result agreed with Obese et al (2013). In contrary, this result disagrees with a previous study (Vendruscolo et al, 2020;Abera et al, 2013;and Goyache et al 2003), they found males grow faster and have higher growth ability. In Contrary, Bayou et al (2015) didn't found any significant differences in weaning weights for both genders.…”
Section: Effect Of Gendercontrasting
confidence: 99%
“…This result agreed with Obese et al (2013). In contrary, this result disagrees with a previous study (Vendruscolo et al, 2020;Abera et al, 2013;and Goyache et al 2003), they found males grow faster and have higher growth ability. In Contrary, Bayou et al (2015) didn't found any significant differences in weaning weights for both genders.…”
Section: Effect Of Gendercontrasting
confidence: 99%